The tectonometamorphic evolution of the Alpine metamorphic belt of the Central Pamir - Dufour, MS; Miller, Yu V (Himalayan Journal of Sciences, 2008)
Himalayan Journal of Sciences Vol.2(4) Special Issue 2004 pp. 131